COST ANALYSIS OF PRIVATE PRIMARY CARE SERVICES lN THREE URBAN CENTES IN MALAYSIA - Syed Mohamed Aljunid; Molly Cheah; Soe Nyunt-U; Kwa SK; Rohaizat Yon; Ding LM (Malaysian Journal of Public Health Medicine, 2001)
A study was undertaken amongst private primary care providers in three urban centres of Malaysia to understand the organizational structure of the facilities and to assess the cost of running such services. A total of 150 clinics were involved in the study. Data was collected through interviews with owners of the clinics using semi-structured questionnaires. Solo-practitioners owned 64.7% of the clinics while 35.3% of them were owned by group practice. This study showed that the mean number of patients visited the clinics daily was 49.3 with the average operating hours of 79.4 hours/week (range 28.0 - 168.0 hours/week). Group practice clinics operates 23.9 hours longer than solo-practice clinics. Group practice clinics were more likely to offer 24 hours service than solo practice clinics. Most of the clinics were manned by a single doctor (57.3%), 30.0 % had two doctors and only I 2. 7% were run by more than two doctors. On average, group practice employed greater number of supporting staff than solo-practice clinics (6.0 vs 4.3 people). The mean annual cost to run each facility was found to be RM 444,698. The mean cost per patient was found to be RM 32.09 for solo-practice clinics and RM 38.55 for group practice. Wages represented the highest proportion in the recurrent cost (61.1%) followed by drugs (29.2%) and consumables (2. 7%). Building cost (67.9%) and equipment cost (25.9%) were the major capital costs for the clinics. This study could serve as a basis to reimburse private primary care providers in the future health financing scheme in Malaysia. To improve efficiency and contain cost in primary care settings, efforts should be targeted towards cost of wages and drugs utilised by the providers in their daily practice.